The Analysis of Correlative Factors of Visual Acuity with Intravitreal Conbercept Injection in Macular Edema Associated with Branch Retinal Vein Occlusion - Wenjuan Luo; Fengjiao Jia; Min Liu; Yunxiao Wang; Ting Zhang (Journal of Ophthalmology)
Purpose. To evaluate the correlative factors of best-corrected visual acuity (BCVA) with intravitreal conbercept injection in macular edema secondary to branch retinal vein occlusion (BRVO). Methods. This is a self-controlled retrospective study. 35 eyes of 35 patients with macular edema secondary to BRVO were enrolled. After an initial intravitreal injection of conbercept (0.5 mg/0.05 ml) monthly up to 3 months, a pro re nata (PRN) strategy was adopted based on the increase in central foveal thickness (CFT). Data collected at various time points include BCVA, CFT, photoreceptor layer thickness (PLT), and outer nuclear layer thickness (ONLT) on optical coherence tomography. The correlation between CFT, PLT, ONLT, and BCVA before and after injections was analyzed. Results. Compared with baseline, in months 1, 3, and 6 after injection, the improvement of BCVA was 20.63, 22.94, and 21.06 ETDRS letters, respectively (F=195.843, P<0.01), and the decrease of CFT was 217.37 μm, 224.57 μm, and 224.06 μm, respectively (F=148.522, P<0.01). The PLT in months 1, 3, and 6 after therapy has significant improvement of 11.14 μm, 13.03 μm, and 13.49 μm (F=64.116, P<0.01), while the ONLT has a significant decrease of 225.29 μm, 237.66 μm, and 239.11 μm, respectively (F=145.231, P<0.01). The changes in the treatment group were significant in different periods. The mean number of injections was 3.26 ± 0.50 from baseline to month 6. Conclusions. Intravitreal injection of conbercept provides an effective treatment for macular edema due to BRVO. With six-month treatment, there were a positive correlation between BCVA and PLT (r=0.592, P<0.001), a negative correlation between BCVA and ONLT (r=−0.480, P=0.005), and no correlation between BCVA and CFT (P=0.506).